Management of investment attractiveness of motor transport enterprises (on the example of Ukraine) - Levchenko, Iaroslava; Левченко, Ярослава (Харківський національний автомобільно-дорожній університет, 2016)
Modern economy is characterized by global processes indicating its crisis state. This period is the most favorable for restructuring the activities of motor transport enterprises (MTE). Such restructuring is connected with the impact of systemic factors on the level of investment attractiveness (IA) of MTEs and efficiency of managing IA of MTEs. The transport sector is vital for economic development of any country. It is a guarantee of the trade turnover, and, consequently, the effective functioning of most of the other economic sectors. Therefore, the rate of economic growth and the population welfare depend on the state of the transport system and efficiency of the functioning of motor transport enterprises. Since the object of the research are the enterprises of motor transport sector of Ukraine, the level of investments attractiveness was identified, the main factors of influencing on the level of motor transport enterprises IA was defined, the elasticity coefficients were calculated, the deviation of the actual index from the optimal one was calculated, a conclusion regarding the need for increasing the values of the factors influencing the level of MTE IA was made.
Управление инвестиционной привлекательностью автотранспортных предприятий (на примере Украины)
Keywords: investments attractiveness; the level of investments attractveness; the elasticity coefficients; the weaknesses and negative effects; motor transport sector of Ukraine; инвестиционная привлекательность; уровень инвестиционной привлекательности; коэффициенты эластичности; слабые стороны и негативные явления; автотранспортная отрасль Украины; 330.322